Investigating Expression of Skin Basal Cell Carcinoma Molecular Biomarkers - Qadir, Chnoor Mohammed Faqe; Khidhir, Karzan Ghafur (Sulaimani Journal for Pure and Applied Sciences, 2020)
Basal cell carcinoma (BCC) of skin is the most common type of human cancer. It is strongly linked with exposure to UV radiations and tumors mostly develop on the sun-exposed skin. Although BCC rarely metastasizes or causes mortality, it can result in broad morbidity through local invasion and causing tissue destruction. Hedgehog signaling pathway (Hh) have been linked to the development of BCC. The aim of this study was to investigate the expression level of the SHH, PTCH1, GLI1, P53 and SMO genes in BCC skin tissue in order to identify reliable biomarkers for clinical applications in the diagnosis of skin BCC. BCC and healthy skin samples were collected from patients who had pre-operation pathological verification, RNA extracted, cDNA synthesized and RT-qPCR was carried out to analyze the expression levels of SHH, PTCH1, GLI1, P53 and SMO genes. Results of the RT-qPCR analysis revealed significant statistical difference in relative expression of SHH, PTCH1, GLI1, P53 and SMO genes between the BCC and healthy tissue groups. The RT-qPCR analysis also showed that expressions of the target genes were upregulated in BCC skin compared to the healthy skin tissue: GLI1 by 3.1 folds, P53 by 0.844 folds, PTCH1 by 4.64 folds, SHH by 1.75 folds and SMO by 2.46 folds. Results of this study suggest that PTCH1 gene can be used as a molecular biomarker for diagnosing BCC of skin. Further studies of the BCC development signalling pathway genes may lead to improved methods for diagnosis and treatment of this common cancer.
Keywords: Basal cell carcinoma; Hh signalling; marker genes; skin